Ku Regulates Signaling to DNA Damage Response Pathways through the Ku70 von Willebrand A Domain - Fell, Victoria L. (American Society for Microbiology, 2012)
The Ku heterodimer (Ku70/Ku80) is a main component of the nonhomologous end-joining (NHEJ) pathway that repairs DNA double-strand breaks (DSBs). Ku binds the broken DNA end and recruits other proteins to facilitate the processing and ligation of the broken end. While Ku interacts with many proteins involved in DNA damage/repair-related functions, few interactions have been mapped to the N-terminal von Willebrand A (vWA) domain, a predicted protein interaction domain. The mutagenesis of Ku70 vWA domain S155/D156 unexpectedly increased cell survival following ionizing radiation (IR) treatment. DNA repair appeared unaffected, but defects in the activation of apoptosis and alterations in the DNA damage signaling response were identified. In particular, Ku70 S155A/D156A affected the IR-induced transcriptional response of several activating transcription factor 2 (ATF2)-regulated genes involved in apoptosis regulation. ATF2 phosphorylation and recruitment to DNA damage-induced foci was increased in Ku70-deficient cells, suggesting that Ku represses ATF2 activation. Ku70 S155A/D156A substitutions further enhanced this repression. S155A substitution alone was sufficient to confer enhanced survival, whereas alteration to a phosphomimetic residue (S155D) reversed this effect, suggesting that S155 is a phosphorylation site. Thus, these findings infer that Ku links signals from the DNA repair machinery to DNA damage signaling regulators that control apoptotic pathways.